Heavy metal (Pb) accumulation in metallophytes as influenced by the variations in rhizospheric and non- rhizospheric Soils physico-chemical characteristics. (2018)
Activities at root-soil interface determine the solubility and uptake of metals by plants. Metal accumulation in plant species (Imperata cylindrical, Cynodon dactylon, Eleucine indica, Gomphrena celosoides, Sporobolus pyramidalis, Chromolaena odorata and Rhynchospora corymbosa) growing on Pb contaminated site as influenced by variations in physico-chemical characteristics, dissolved organic matter (DOM), Pb fractionation and different functional groups (using Fourier Transmittance Infra-red) of rhizospheric and non-rhizospheric soils was assessed. The electrical conductivity (2660–5520 ms) and Pb concentrations (51390.0–64080.0 mg/kg) were more in non-rhizospheric than rhizospheric soils having 276 ms to 3160 ms EC and 3289.0 to 44850.0 mg/kg Pb. More nutrients, DOM and carbohydrates functional groups (C-O; 1100 -1000 and O-H; 3700–3600) were found in rhizospheric compared to non-rhizospheric soils. The pH was slightly acidic (5.0–5.54) and E. indica with the lowest pH (5.0) accumulated highest Pb concentrations in shoot (8030 mg/kg) and root (16380 mg/kg) while C. odorata with highest values of pH, P, Ca and Mg in rhizospheric soil accumulated the least (root; 331.6 and shoot: 209.0 mg/kg). Pb was more in organic and residual fractions of rhizospheric and non-rhizospheric soils respectively. Reduction in pH, EC coupled with nutrients and DOM availability increased Pb uptake by plants.